Stratospheric NO2 concentration determined by DOAS using compact spectrographs - Raponi, Marcelo Martín (2008)
In this work we present the results for stratospheric NO2-total column concentration retrieved by DOAS (Differential Optical Absorption Spectroscopy) performed with compact spectrographs. The behavior for three different spectrographs (MonoSpec 27, Jarrell-Ash; HR4000, Ocean Optics and Mechelle 900, Multichannel Instruments) are analyzed making one intercomparison in the facilities of the LIDAR Division of CEILAP (CITEFA - CONICET), in Villa Martelli, Argentina (34.5° S, 58.5° W, 20 m amsl). The three instruments have a similar resolution (approximately 0.1 nm) but operate with different optical configurations and have optical sensors of different characteristics; two of them have cooling capability and the other one (HR4000) operates at room temperature. The NO2 concentration was obtained from spectral results at twilight using solar noon spectra as reference. In all cases zenithal diffuse irradiance was used. The NO2 absorption cross section given by S. Voigt and J. P. Burrows (University of Bremen - Institute of Environmental Physics) corresponding to 223°K and 100 mbar is used. Results are compared with public data corresponding to ground-based device or to instruments mounted in satellites. These atmospheric soundings are of extreme importance to understand the roll that plays the stratospheric NO2 in the associated phenomena of destruction and formation of ozone in the low stratosphere at middle latitudes.